The correlation between hypertension and low fetal weight in Palembang city, Indonesia - Zata Ismah; Sri Wahyuni; Wan Rizky Chairunnisa; Annisa D.A.SS. Angkat (Fakultas Kedokteran Universitas Gadjah Mada, 2018)
Hypertension as one of health problem that often occurs during pregnancy is epidemiological evidence that can affect the incidence of small for gestational age. The purpose of this study is to determine the effect of hypertension on the incidence of low fetal weight. This study is using a cross-sectional design with a total of 752 samples in 25 selected health services taken by accidental sampling method. The results showed a significant association between hypertension with incidence of low fetal weight. The prevalence of hypertensive women experienced a low of fetal weight is at 7,272 times (95% CI 3,415-15,482) greater than those who are not hypertensive. The odds of low fetal weight in hypertensive women were 24.1%. Early intervention by carrying out activities in the form of female chronic hypertension screening before the pregnancy phase may reduce the risk of low fetal weight due to hypertension